Cold Turkey and Hot Vapes? A National Study of Young Adult Cigarette Cessation Strategies. Issue 5 (26th December 2018) - Watkins, Shannon Lea; Thrul, Johannes; Max, Wendy; Ling, Pamela M
Abstract: Introduction: Young adults have high smoking rates and low utilization of evidence-based smoking cessation strategies. We investigated smoking cessation intentions, strategy use, and socioeconomic predictors of strategy use among young adult smokers (age 18–24) and compared patterns with those of older adults (age 25–64). Methods: We used a population-based sample from the Population Assessment of Tobacco and Health (PATH) study of young adult ( n = 1, 881) and older adult ( n = 6, 366) established smokers of conventional cigarettes at Wave 1 (2013–2014), who were surveyed at Wave 2 (2014–2015). Simple regression analysis compared intentions to quit between age groups. Among Wave 1 smokers who reported a Wave 2 quit attempt (young adults [YA] n = 748; older adults [OA] n = 2, 068), bivariate and multinomial logistic regression estimated differences in use of behavioral support, pharmacotherapy, product substitution, and unassisted quit attempts. Interaction terms estimated age-group differences in relationships between predictors and cessation strategy use. Results: Young adults planned to quit on a longer time frame, expressed lower interest in quitting, and were more confident they would be successful, compared with older adults. Young adults were significantly less likely to use pharmacotherapy (adjusted odds ratio: 0.15; confidence interval: 0.09, 0.24; reference: quitting unassisted). Both groups reported using product substitution (YA: 31.6%; OA: 28.5%), primarily with e-cigarettes, more than any evidence-based cessation strategy. Socioeconomic predictors of cessation strategy use did not differ between age groups. Conclusions: More research on why young adult smokers underutilize evidence-based cessation support is needed, as are innovative efforts to increase intentions to quit and utilization of cessation assistance. Implications: Young adulthood is a key transition time for tobacco use, and early cessation substantially reduces the risk of morbidity and mortality from smoking. In the context of high e-cigarette and polytobacco use, this study finds young adults have significantly less intention to quit than older adults and are less likely to use evidence-based cessation strategies to help quit. Innovative methods are needed to increase young adult intentions to quit and use of evidence-based cessation assistance.